2015
DOI: 10.1007/s11695-015-1712-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Laparoscopic Sleeve Gastrectomy and Roux-en-Y Gastric Bypass in Patients Older than 60

Abstract: Bariatric surgery can be safe and effective for patients older than 60 years of age with a low morbidity and mortality; the weight loss and improvement in comorbidities in older patients were clinically significant. When compared to the general population, there was no statistically significant difference in the average %EWL at 12 months or the number of complications due to surgery. Long-term effects of such interventions will need further studies and investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 19 publications
3
37
0
2
Order By: Relevance
“…15 Abbas et al also recently reported that both LSG and laparoscopic RYGBP could be safely and effectively carried out for patients aged >60 years. 16 In accordance with these reports, the present results show that LSG for patients aged >60 years is safe and of considerable benefit.…”
Section: Discussionsupporting
confidence: 92%
“…15 Abbas et al also recently reported that both LSG and laparoscopic RYGBP could be safely and effectively carried out for patients aged >60 years. 16 In accordance with these reports, the present results show that LSG for patients aged >60 years is safe and of considerable benefit.…”
Section: Discussionsupporting
confidence: 92%
“…Of 38 studies comparing the safety of bariatric procedures in older vs younger groups, 16 found no difference in early mortality or complication rates between groups . A further four studies found no difference between groups in overall complications, but higher rates of certain events in older participants, such as cardiac complications, intubation for longer than 48 hours, acute kidney injury, sepsis and pulmonary embolus, and bleeding .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 28 studies in which weight outcomes for older and younger persons were compared, 16 found no significant difference in weight loss between groups, and seven studies reported less weight loss in older than younger participants . Greater total weight loss in younger participants but no difference in percent excess weight loss (%EWL) between groups was reported in two studies .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations